CENTRAL EUROPEAN ENTANGLEMENTS AND WOMEN'S HISTORY: A CASE STUDY (Journal of Contemporary Philology, 2025)
This paper examines the intellectual and political entanglements of Alžbeta Göllnerová Gwerková (1905–1944), a Slovak scholar, translator, and activist whose work exemplifies  the intersections of gender, culture, and politics in interwar Czechoslovakia. Positioned as both a supporter of Czechoslovakism and a mediator of Hungarian culture, Göllnerová Gwerková consciously inserted herself into academic discourse as a political actor. Her  writings reveal a dual commitment: on the one hand, to democratic and liberal ideals that sought to transform estate society into civic society; on the other, to the promotion of  Czechoslovak unity as a cultural and political project. The paper highlights how her  feminist awareness, which started to take shape in the mid-1930s, intersected with her scholarly endeavors and with her marginal position in academia. By revisiting her  intellectual biography, the study foregrounds the political dimension of her scholarship and argues for her reintegration into the history of Central European humanities. The paper also  seeks to demonstrate that Slovak feminine identities are deeply entangled in the cultural dynamics of a small, non-dominant nation – an entanglement that shapes women's biographies and influences their intellectual work.
Keywords: Alžbeta Göllnerová-Gwerková; Czechoslovakism; interwar culture; humanities